Validation of the Peruvian Spanish Version of the Stress and Anxiety to Viral Epidemics-6 Scale to Measure Viral Anxiety of Medical Students During COVID-19 - Lapeyre-Rivera, André; Javier-Murillo, Nair; Perea-Flórez, Francisco; Gamonal, Bryan; Velásquez-Rimachi, Víctor; Alva-Díaz, Carlos; Ahmed, Oli; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
Introduction: The COVID-19 pandemic has created academic problems for Peruvian medical students leading to anxiety and depression. Hence, validated scales, such as the Stress and Anxiety to Viral Epidemics-6 items scale (SAVE-6), are required to identify and propose interventions to improve mental health. We aimed to perform a psychometric validation of the Peruvian version of SAVE-6 on medical students at the National University of San Marcos during the COVID-19 pandemic in Peru, in 2022. Methods: A total of 260 students participated in an online survey in January 2022. We collected sociodemographic characteristics and classified psychiatric symptoms using SAVE-6, the Generalized Anxiety Disorder-7 items (GAD-7) scale, and the Patient Health Questionnaire (PHQ-9). We performed confirmatory and parallel factor analysis to examine the validity of the Peruvian Spanish version of SAVE-6. Results: We explored the reliability and validity of SAVE-6 and SAVE-6 after excluding item 5, since factor loading of item 5 is too low.. Both scales showed good internal consistency (Cronbach’s α = .780 & .82 and McDonald’s Ω = .792 & .829, respectively). Furthermore, SAVE-6 after excluding item 5 showed good convergent validity with GAD-7 (r=0.224, p<0.001) and PHQ-9 (r=.217, p<0.001). Consequently, instead of the full SAVE-6, SAVE-6 excluding item 5 proved to be reliable and valid enough to assess the anxiety of Peruvian medical students during the pandemic. Conclusion: The Peruvian Spanish SAVE-6 scale excluding item 5, rather than the full SAVE-6, can be applied to measure viral anxiety of medical students in Peru with good validity and reliability.